Systems Biology Approaches to Understand Natural Products Biosynthesis - Licona-Cassani, Cuauhtemoc; Cruz-Morales, Pablo; Manteca, Angel; Barona-Gomez, Francisco; Nielsen, Lars K.; Marcellin, Esteban (Frontiers in Bioengineering and Biotechnology, 2015)
Actinomycetes populate soils and aquatic sediments which impose biotic and abiotic challenges for their survival. As a result, actinomycetes metabolism and genomes have evolved to produce an overwhelming diversity of specialized molecules. Polyketides, non-ribosomal peptides, post-translationally modified peptides, lactams and terpenes are well known bioactive natural products with enormous industrial potential. Accessing such biological diversity has proven difficult due to the complex regulation of cellular metabolism in actinomycetes and to the sparse knowledge of their physiology. The past decade, however, has seen the development of omics technologies that have significantly contributed to our better understanding of their biology. Key observations have contributed towards a shift in the exploitation of actinomycetes biology, such as using their full genomic potential, activating entire pathways through key metabolic elicitors and pathway engineering to improve biosynthesis. Here, we review recent efforts devoted to achieving enhanced discovery, activation and manipulation of natural product biosynthetic pathways in model actinomycetes using genome-scale biological datasets.